Forest vs Savanna dynamics in the contact zones of French Guiana - Gaëlle Viennois; Eric A. Nicolini; Frédéric Borne (Revue Française de Photogrammétrie et de Télédétection, 2014)
Savannas and tropical forests delineated by sharp boundaries are two alternative stable ecosystems. What is the natural evolution of forests over savannas in coastal savanna in French Guiana? The dynamic balance between forest advance and retreat is a response to disturbances such as fire or extreme drought events. Fire maintains savanna by its action on forest-savanna contact areas, while a dry climate prevents forest expansion. This paper focuses on coastal savannas of French Guiana nested in the Guiana Space Center (CSG) that is occasionally threatened by bushfires in the dry season. This study spanned over 60 years of landscape changes around the CSG and used a georeferenced set of aerial and Pléiades satellite images. Forest and savanna dynamics were mapped and highlighted with the computing of shape indicators. This study showed that the forest progressed of 23% onto savanna and mainly at the forest—savanna contact zones.